Exercise countermeasure preferences of three male astronauts, a preliminary qualitative study. (December 2022) - Laws, J.M.; Bruce-Martin, C.; Caplan, N.; Meroni, R.; Winnard, A.
Abstract: Background: A single flywheel exercise countermeasure has been chosen for use on-board the Orion Multi-Purpose Crew Vehicle for spaceflight missions of up to 30 days. As previous missions have typically involved the use of multiple exercise countermeasures there is a concern that the use of only flywheel may lead to boredom and reduce astronaut adherence to exercise prescriptions, presenting a risk to their health and the operational success of the mission. To determine if this will be a concern, this qualitative work identified astronaut-reported operational considerations for the implementation of an exercise countermeasure device for use during spaceflight, and if current plans for the implementation of a single flywheel exercise countermeasure device may affect astronaut adherence to exercise prescriptions. Methods: The responses of three male astronauts to an open-ended qualitative survey were analysed using thematic analysis. All participants were required to currently be taking part in, or have previously taken part in, human spaceflight. Results: Astronaut preferences for the use of an exercise device during spaceflight were categorised into three broad themes: exercise device ease of access, motivational and behavioural considerations, and operational and technical considerations. The three astronauts considered a single flywheel-based exercise device suitable for use as the sole exercise countermeasure on-board the Orion MPCV, and similar capsular spacecraft, so long as it met several conditions. The device should engage astronauts in a varied exercise prescription. The device should also meet the physiological expectations required of exercise countermeasures for spaceflight deconditioning. The device should be enjoyable to use, and measures should be put in place to reduce boredom (via variety in exercise prescription). The device should be easy to access in terms of both use and setup/takedown. Finally, the device should only be used without other exercise countermeasures for missions of 30 days or less. Conclusion: Individual crewmember preferences should be taken into consideration following crew selection to ensure the greatest adherence to exercise prescriptions. The data reported here should be used to supplement, not entirely inform, the development and use of future exercise countermeasures. Highlights: A single exercise device may be suitable if it meets astronaut expectations. Variety in exercise prescription may increase adherence. Individual crewmember preferences should be taken into consideration.